Genome-wide RNAi Screen Identifies Romo1 as a Novel Regulator of Mitochondrial Fusion and Cristae Integrity - Norton, Matthew (Université d'Ottawa / University of Ottawa, 2013)
Mitochondria exist in a dynamic network regulated by the opposing processes of mitochondrial fusion and fission. Regulation of mitochondrial morphology is critical for metabolism, quality control and cell survival, among other cellular processes. Large GTPases are responsible for shaping the mitochondrial network. Mitofusins 1 and 2 and Opa1 regulate outer and inner mitochondrial membrane fusion, respectively. Conversely, Drp1 is recruited to mitochondria to carry out fission. Although many proteins have been implicated in these processes, there are still many unknowns. We sought to identify novel regulators of mitochondrial morphology and conducted a genome-wide RNAi screen to identify candidate genes. We identified Reactive Oxygen species Modulator 1 (ROMO1) as a novel regulator of mitochondrial fusion and cristae integrity. In the absence of ROMO1, the mitochondrial network fragments and cristae are lost. These defects lead to impaired mitochondrial respiration and sensitization to cytochrome c release and downstream apoptosis. ROMO1 is regulated by mitochondrial REDOX at 4 cysteine residues that couple REDOX signaling to mitochondrial morphology. We have characterized ROMO1 as an interactor with the MINOS complex, required for cristae junction maintenance, and the inner mitochondrial membrane fusion GTPase OPA1. Through these interactions ROMO1 couples cristae junction security to mitochondrial fusion.
Keywords: Mitochondria; Mitochondrial Dynamics; Mitochondrial Fusion; ROMO1; OPA1; ROS; REDOX; Cristae; Apoptosis